STUDENTS’ VOICE OVER TECHNOLOGY-BASED SPEAKING CLASS - Yesika Maya Ocktarani (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
During the Covid-19 pandemic, not only teachers, English Learners have to deal with new media in their online speaking classes.  At the end of the class, they may be satisfied with the learning result but some of them may be disappointed. Previous researches claim that students have different perceptions of the success of using a certain platform for gaining their speaking skills. However, the perception of students in using combined-platforms in speaking class remains indefinite. Therefore, instead of measuring the effectiveness of certain platforms in achieving learning targets, this study aims to observe students’ perception of their speaking ability. To achieve this goal, 37 participants from Basic Speaking Class get involved in portraying their speaking skills and how effective are the used platforms during the class. As descriptive qualitative research, this study analyses students’ responses as the main data from the interview regarding the use of WhatsApp, Flipgrid, and Zoom platforms to enhance their speaking skills. As a result, most of the students believe that the combination of those platforms enhances their speaking ability and only a few students remain unsure due to unsatisfied scores. The result of this study paves the way for English teachers to design more student-friendly syllabus which considering students point of view in using technology for speaking class